A Design Tool for Clothing Applications: Wind Resistant Fabric Layers and Permeable Vents. (18th November 2014) - Gibson, Phillip; Sieber, Michael; Bieszczad, Jerry; Gagne, John; Fogg, David; Fan, Jintu
Abstract : A computational clothing design tool is used to examine the effects of different clothing design features upon performance. Computational predictions of total heat and mass transfer coefficients of the clothing design tool showed good agreement with experimental measurements obtained using a sweating thermal manikin for four different clothing systems, as well as for the unclothed bare manikin. The specific clothing design features examined in this work are the size and placement of air-permeable fabric vents in a protective suit composed primarily of a fabric-laminated polymer film layer. The air-permeable vents were shown to provide additional ventilation and to significantly decrease both the total thermal insulation and the water vapor resistance of the protective suit.